Resiliensi dan Adaptasi UMKM Sasirangan di HST: Membangun Model Bisnis Kreatif Berbasis Komunitas untuk Ketahanan Ekonomi Lokal - Burhannudin, Burhannudin; Sri Rahayu (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS SAPTA MANDIRI, 2026)
This study examines the resilience strategies, adaptive mechanisms, and the development of community-based creative business models among Sasirangan SMEs in Hulu Sungai Tengah, South Kalimantan, within the context of economic uncertainty and shifting market preferences. A qualitative descriptive approach was employed, utilizing data collected through observations, in-depth interviews, and document analysis involving SME actors, local communities, and relevant stakeholders. The findings indicate that Sasirangan SMEs demonstrate adaptive resilience through product diversification, operational flexibility, and active engagement in social networks and community collaboration, enabling sustainable operations while enhancing competitiveness. The implementation of community-based creative business models, which integrates local wisdom, product innovation, and digital technology, contributes to market expansion and the preservation of Sasirangan cultural heritage. These results underscore the significance of policy support for strengthening digital literacy, facilitating culture-based innovation, and fostering community networks as critical factors for SME sustainability. Furthermore, this study provides implications for future research to investigate strategies for measuring SME resilience, the impact of digitalization on the sustainability of culture-based enterprises, and the optimization of creative business models that are more adaptive and inclusive.